The Influence of Prior Experince, Variety Seeking and Product Knowledge on Brand Switching - Fathma Eviyana Rosyidah; Lilik Nur Cholidah; Moh Muklis Sulaeman (Journal of Business Innovation and Accounting Research, 2025)
Beauty companies are very competitive, with many brands popping up by creating similar products to gain market share. This study aims to determine the influence of Prior Experience, Variety Seeking, and Product Knowledge on Brand Switching. The population in this study is Wardah consumers in Lamongan. This research uses quantitative research methods. Using purposive sampling and the Slovin formula, the sample size was determined to be 94 respondents. The results of the study show that the variety seeking variable for brand switching has a negative and significant effect. Meanwhile, Prior Experience and Product Knowledge on Brand Switching have a positive and significant effect. Based on the R2 (coefficient of determination) results for the Prior Experience, Variety Seeking, and Product Knowledge factors, Brand Switching was affected by 68.7%, with the remaining 31.3% attributable to variables not studied in this study. This research contributes to the understanding of consumer decision-making in the beauty sector, highlighting the complex role of experience, knowledge, and the search for variety in shaping brand preferences. Further research can explore additional variables influencing Brand Shift to provide a more comprehensive understanding of consumer behaviour in a highly competitive industry.